Estudo dos campos vetoriais polinomiais quadráticos que possuem integral primeira racional de grau 3 - Cruz, Claudemir Mota da (2011)
This work was dedicated to classify all the global phase portraits of the quadratic polynomial vector fields having a rational first integral of degree three. For this, techniques were used as blow-up, classification of singular points, invariant curves for a system of ordinary diferential equations and vector fields induced on the sphere.